Improving lives not just saying no to substances: Evaluating outcomes for a young people's substance use team trained in the AMBIT approach. (April 2021) - Fuggle, Peter; Talbot, Laura; Wheeler, James; Rees, Jessica; Ventre, Emily; Beehan, Verity; Hare, Suzanne; Bevington, Dickon; Cracknell, Liz
Adaptive Mentalization Based Integrative Therapy (AMBIT) is a systemic, mentalization based intervention designed for young people with multiple problems including mental health problems. The purpose of this paper is to examine the impact of this approach both on clinical and functional outcomes for young people seen by a specialist young people's substance use service between 2015 and 2018. About 499 cases were seen by the service during this period. Substance use outcomes were obtained for 383 cases using the Treatment Outcome Profile (TOP). Cannabis and alcohol use were the key substance use problems for 81% and 63% respectively. Functional outcomes using the AMBIT Integrative Measure (AIM) were obtained for 100 cases covering domains of daily living, socio-economic context, peer relationships and mental health. At treatment end, cannabis use reduced significantly ( t = 10.78; df = 311; p = .00; Cohen's d ES.61 as did alcohol use ( t = 6.938; df = 242; p = .000; ES 0.44). Functional improvements were shown in five out of seven domains with highly significant total functional improvements on key problems selected by the client ( t = 14.01; df = 99; p = .000; ES1.34). Measuring functional as well as clinical outcomes appears to reflect more accurately the overall benefit of the service to clients.